Superimposed Stress Calculation of Soil Underlying Anchor Beam considering Anisotropy and Strength Nonhomogeneity. (10th September 2022) - Xu, Fei; Wang, Zhongshun; Zhou, Liming; Zheng, Hemin; Liu, Bo; Jiang, Yuqiu; Wang, Daili
Abstract : Prestress anchor beams are an important reinforcement method for underground engineering and rock slopes, and they are crucial for maintaining the stability of civil engineering structures. In this study, the computational formula of superimposed stress of soil underlying an anchor beam was proposed in this paper, based on the assumption that the anchor beam is completely rigid and the prestress of the anchor cable is acting on soil in the form of a strip uniform load. By considering the anisotropy and strength nonhomogeneity of the saturated soft clay, the failure envelopes of the soil and the maximum effective depth underlying the anchor beam were obtained by the D-P yield criterion suitable for soft clay analysis. Furthermore, the experimental comparisons with the previous findings were used to validate the proposed approach. The proposed method was valid to assess the maximum effective depth. Considering the influence of the factors on the failure envelopes of soil, a parametric study was carried out to optimize the design of the prestressed anchor cable. The findings of this study provide a theoretical basis for designing prestressed anchor cables; these can also be used to predict the response of prestressed anchor cables as well as to optimize the design of the cables, such as the anchorage length of cable and grouting radius.